Adaptation of visible and short wave Near Infrared (VIS-SW-NIR) common PLS model for quantifying paddy hardness - Awanthia, M.G.G.; Jinendra, B.M.S.; Navaratne, S.B.; Navaratne, C.M. (Elsevier, 2019)
Hardness of paddy is an indicator of preserved quality of rice as it maintains the integrity of grain to avoid falling-off during milling. Most of the prevailing methods carter to determine the hardness are destructive and time consuming. Though, use of Near Infrared (NIR) is nondestructive, its conventional approach implies separate Partial Least Square (PLS) model for each new paddy type to be predicted successfully. Therefore, this study evaluates NIR spectroscopy (588–1091 nm) to be used as a common PLS model for quantifying a range of paddy varieties and processing conditions in rapid and non-destructive mode. The acquired NIR spectra were used to construct PLS calibration models by using Pirouette 4.5 software. As a result, the lowest standard error of validation (SEV=1.711) and highest correlation coefficient of validation (R2=0.936) were obtained. The research has successfully demonstrated that the potential possibility of NIR spectroscopy to be used as a common PLS model for quantifying hardness of paddy from new varieties and conditions
Keywords: Hardness Near infrared Non destructive Paddy Spectroscopy